2003
DOI: 10.1021/ie020837y
|View full text |Cite
|
Sign up to set email alerts
|

Gibbsite to Boehmite Transformation in Strongly Caustic and Nitrate Environments

Abstract: The transformation of gibbsite to boehmite in strongly caustic solutions was studied using quantitative X-ray diffraction, Fourier transform infrared spectroscopy, and transmission electron microscopy techniques. Under hydrothermal conditions, we identified two transformation mechanisms: (1) dehydration and in situ nucleation and (2) dissolution and nucleation. If the reaction container was not completely sealed, dehydration of gibbsite followed by in situ nucleation of boehmite was the preferred mechanism. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…This conclusion is consistent with the conversion mechanisms described elsewhere [23,46,47]. Calcite and sodalite precipitation were not observed in the fused silica capillary experiments; changes in calcite:anatase ratio in Table 2 indicate that this is a slower reaction and smaller in magnitude than the boehmite precipitation reaction.…”
Section: Solids Mineralogysupporting
confidence: 90%
See 2 more Smart Citations
“…This conclusion is consistent with the conversion mechanisms described elsewhere [23,46,47]. Calcite and sodalite precipitation were not observed in the fused silica capillary experiments; changes in calcite:anatase ratio in Table 2 indicate that this is a slower reaction and smaller in magnitude than the boehmite precipitation reaction.…”
Section: Solids Mineralogysupporting
confidence: 90%
“…The n values of 0.8-1.2 observed for gibbsite dissolution (Table 4) are consistent with first-order reaction kinetics (n = 1). Contracting area kinetics, with an n value of 1.04, and contracting volume kinetics, with an n value of 1.08, would also be feasible explanations for the observed n values and are consistent with the transformation of gibbsite to boehmite as a dissolution-precipitation mechanism [46,47]. Table 3.…”
Section: Reaction Kineticssupporting
confidence: 54%
See 1 more Smart Citation
“…It is known that gibbsite readily dissolves at moderate hydroxide concentrations and moderate temperatures, while boehmite dissolution requires more rigorous conditions and generally is kinetically slow. Gong et al 22) found that gibbsite [¡-Al(OH) 3 ] dissolved into a basic solution with sodium hydroxide and then crystallized as boehmite. Consequently, in the pseudoboehmite nanocrystal formation process of the present study, alumina constituents in the precursor amorphous gel film first dissolve in water.…”
Section: Formation Process Of Flowerlike Aluminamentioning
confidence: 99%
“…Fresh HLW slurries can self-heat due to radioactive decay, frequently reaching temperature of 100 -150 °C. 4 We performed a series of experiments designed to examine the effect of other common cations present in the HLW on the phase of aluminum formed.…”
Section: Introductionmentioning
confidence: 99%